The Socio-Ethical Tafsir of Sayyid Qutb - Amir, Ahmad Nabil; Tasnim Abdul Rahman, Tasnim Abdul Rahman (Universitas Islam Negeri Raden Intan Lampung, 2025)
The paper analysed the essential methodology adopted by Sayyid Qutb in his Tafsir Fî Zilâl al-Qur'an and its instrumental role in projecting a modern Islamic outlook based on his social and dynamic exegetical orientation. Its objective is to identify the exegetical school he propounded and its role in shaping the modern Islamic worldview based on his social interpretation. The study is based on qualitative approaches in the form of textual analysis and a library survey. By using the Miles & Huberman model, it gathered related primary and secondary literature in the field. The data were analyzed based on Qutb's socio-ethico concept. The finding shows that Sayyid Qutb had formulated an inclusive method of philosophical interpretation of the Qur'an that established socio-linguistic and ethico-legal principles as its core ideological roots and basis. The pattern of thought and interpretation was influenced by this idea, reflecting the dynamic (haraki) framework it conceived in the development of his tafsir. This categorically forms the basis of his philosophy and idealism, which underlies its socio-religious outlook and its relevance in shaping the modern Islamic generation to revitalise the cultural-linguistic aspect and perennial values of tawhid in the modern narrative of dakwah.